Fatores associados ao estresse de cuidadores familiares de crianças e adolescentes com Síndrome de Down - Martins, Bianca Annie (Universidade Federal de São Carlos, 2024)
To analyze the stress of family members of children and adolescents with Down syndrome and identify associated factors. Method: Observational, analytical, and cross-sectional study with a quantitative approach, conducted in five neighboring cities located in the central region of the state of São Paulo. Data collection was performed in the homes, through the application of a sociodemographic characterization instrument, a perceived stress scale, and collection of salivary cortisol upon awakening. Bivariate and multivariate statistical analyses were performed. Ethical aspects were respected. Results: Thirty family members participated, 24 mothers, five fathers, and one sister. The average score for perceived stress was 31.9 points. The average salivary cortisol upon awakening was 0.44 µg/dL. Statistical significance was observed between cortisol and occupation. No sociodemographic variable was associated with perceived stress. Conclusion: A tendency toward low cortisol levels and high levels of perceived stress was observed among family members. Those with paid employment showed increased levels of salivary cortisol compared to family members without employment.
Factors associated with stress in family caregivers of children and adolescent with Down Syndrome
Keywords: Criança; Adolescente; Família; Síndrome de Down; Estresse; CIENCIAS DA SAUDE::ENFERMAGEM